The primary culture and subculture of kidney-derived cells of the bony lip barb fish (Osteochilus vittatus) using different concentrations of serum - Firdauzi, Alif Arfa Maulida; Wijayanti, Gratiana Ekaningsih; Habibah, Aulidya Nurul (Proceeding ICMA-SURE; Proceeding The 5th International Conference on Multidisciplinary Approaches for Sustainable Rural DevelopmentDO - 10.20884/2.procicma.2023.2.1.7818, 2023)
Cell and tissue culture have advanced and developed in a short time yet continuous improvement needs to be conducted for better results. This research was conducted to obtain suitable culture conditions of kidney-derived cell culture from bony lip barb kidney ( Osteochilus vittatus ). The development of primary cell culture from the kidney fragments was performed in a cell culture medium composed of DMEM supplemented with various concentrations (0%, 5%, 10%, and 15%) of Fetal Bovine Serum, Penicillin-Streptomycin, and 2Mm L-Glutamine, and incubated at 29°C with 0.8% CO 2 . The results showed that the primary cell culture achieved confluence on day four and subsequently subcultured. The addition of 10% serum increased cell density and cell survival. The cell morphological evaluation using a phase-contrast microscope showed two dominant cell types for both primary and subcultures, i.e. erythrocytes and small-rounded cells. The highest cell yield was obtained with the addition of 10% serum concentration with Population Doubling Time (PDT) and Population Doubling Level (PDL) for 69 h 23 min and 0.47 times, respectively. Statistical analysis indicated that serum addition significantly increased cell density of the primary culture (p<0.05). A better proportion of serum supplementation to culturing success is essential to establish an auspicious cell line.